2013
DOI: 10.1158/0008-5472.can-13-0755
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Prostate Cancer by d,l-Sulforaphane Is Augmented by Pharmacological Inhibition of Autophagy

Abstract: There is preclinical evidence that oral administration of D,L-sulforaphane (SFN) can decrease the incidence or burden of early-stage prostate cancer (PIN) and well-differentiated cancer (WDC), but not late-stage poorly differentiated cancer (PDC). Because SFN treatment induces cytoprotective autophagy in cultured human prostate cancer cells, the present study tested the hypothesis that chemopreventive efficacy of SFN could be augmented by pharmacological inhibition of autophagy using chloroquine (CQ). Incidenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 51 publications
3
51
0
1
Order By: Relevance
“…It has previously been reported that the combination of SFN with autophagy inhibition, by 3-MA or bafilomycin A1, may be a promising strategy for breast cancer (29), human colon cancer (30) or human prostate cancer (8) therapy. Furthermore, the chemopreventive efficacy of SFN may be augmented by inhibition of autophagy using chloroquine in a transgenic adenocarcinoma of mouse prostate as shown in an in vivo study (31). The present study showed that the inhibition of autophagy by 3-MA does not alter …”
Section: A B Csupporting
confidence: 54%
“…It has previously been reported that the combination of SFN with autophagy inhibition, by 3-MA or bafilomycin A1, may be a promising strategy for breast cancer (29), human colon cancer (30) or human prostate cancer (8) therapy. Furthermore, the chemopreventive efficacy of SFN may be augmented by inhibition of autophagy using chloroquine in a transgenic adenocarcinoma of mouse prostate as shown in an in vivo study (31). The present study showed that the inhibition of autophagy by 3-MA does not alter …”
Section: A B Csupporting
confidence: 54%
“…SFN can downregulate the expression of β-catenin through activation of caspase-3 in human cervical carcinoma HeLa and hepatocarcinoma HepG2 cells. The combination of SFN and chloroquine significantly reduce the incidence as well as size of lymph node metastasis by inhibiting EMT and suppressing proangiogenic cytokine vEGF in prostate cancer compared with control group (22). SFN counteracts aggressiveness of pancreatic cancer driven by dysregulated Cx43-mediated gap junctional intercellular communication (47).…”
Section: Discussionmentioning
confidence: 99%
“…Sulforaphane (SFN), a naturally-occurring member of the isothiocyanate (ITC) family, is ample in normally consumed cruciferous vegetables (22,23). Recently, evidence from numerous epidemiological investigations demonstrated that the higher dietary intakes of cruciferous vegetables were associated with reduced risk of various cancers, such as mammary gland tumorigenesis, colonic aberrant crypt foci, stomach tumors, prostate, bladder and lung cancer (24).…”
Section: Introductionmentioning
confidence: 99%
“…Prostate adenocarcinoma remains a leading cause of cancer mortality among American men despite a comprehensive understanding of the underlying biology, genomic landscape, and the risk factors (9-12). Population-based evidence prompted us to test the efficacy of PEITC and SFN for prevention of prostate cancer using a transgenic mouse model (Transgenic Adenocarcinoma of Mouse Prostate; TRAMP) (13-15). Dietary administration of PEITC (3 μmol/g diet) for 19 weeks to male TRAMP mice resulted in a statistically significant decrease in the incidence of poorly-differentiated prostate cancer when compared to mice fed with basal diet (13).…”
Section: Introductionmentioning
confidence: 99%